The Potential of Streptomyces spp. from Mangrove Land to Control Root-Knot Nematodes - Chowasil Ma'budah; Penta Suryaminarsih; Wiwin Windriyanti (The University of Lampung, 2026)
Nematode attacks on tomato plants can be controlled using Streptomyces spp. The search for new Streptomyces isolates in mangrove lands is important because they can produce secondary metabolites potential to suppress nematodes. This study aims to determine the ability of Streptomyces spp. to control nematodes in vitro and inhibit root-knot formation. The in vitro test study was arranged in a factorial completely randomized design with three replications. The first factor was Streptomyces isolates from 2 different mangrove lands, namely Gunung Anyar (Surabaya) and Banyurip (Gresik.). The second factor was application concentration (10% and 20%). Data was analyzed using ANOVA continued with DMRT a confidence level of 95% (α = 5%). Results showed that Streptomyces have significant nematicidal activity against J2 of the nematode M. Incognita with Juvenile 2 (J2) mortality rates found to be higher at a concentration of 20% compared to 10%, and mortality rates increased for up to 48 h. The study showed that Streptomyces spp. from the mangrove lands has the potential as a nematicide for J2 root-knot nematode in cherry tomato plants. Treatment with Streptomyces spp. at a concentration of 20% resulted in the highest mortality of 60.21% for Gunung Anyar isolate and 58.33% for Banyurip isolate.